Preconditioning With Natural Microbiota Strain Ochrobactrum vermis MYb71 Influences Caenorhabditis elegans Behavior - Petersen, Carola; Pees, Barbara; Martínez Christophersen, Christina; Leippe, Matthias (Frontiers in Cellular and Infection Microbiology, 2021)
In comparison with the standard monoxenic maintenance in the laboratory, rearing the nematode Caenorhabditis elegans on its natural microbiota improves its fitness and immunity against pathogens. Although C. elegans is known to exhibit choice behavior and pathogen avoidance behavior, little is known about whether C. elegans actively chooses its (beneficial) microbiota and whether the microbiota influences worm behavior. We examined eleven natural C. elegans isolates in a multiple-choice experiment for their choice behavior toward four natural microbiota bacteria and found that microbiota choice varied among C. elegans isolates. The natural C. elegans isolate MY2079 changed its choice behavior toward microbiota isolate Ochrobactrum vermis MYb71 in both multiple-choice and binary-choice experiments, in particular on proliferating bacteria: O. vermis MYb71 was chosen less than other microbiota bacteria or OP50, but only after preconditioning with MYb71. Examining escape behavior and worm fitness on MYb71, we ruled out pathogenicity of MYb71 and consequently learned pathogen avoidance behavior as the main driver of the behavioral change toward MYb71. The change in behavior of C. elegans MY2079 toward microbiota bacterium MYb71 demonstrates how the microbiota influences the worm’s choice. These results might give a baseline for future research on host–microbiota interaction in the C. elegans model.